5x-3x-2x=6

Simple and best practice solution for 5x-3x-2x=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3x-2x=6 equation:


Simplifying
5x + -3x + -2x = 6

Combine like terms: 5x + -3x = 2x
2x + -2x = 6

Combine like terms: 2x + -2x = 0
0 = 6

Solving
0 = 6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -x-5=20 | | 3000=1500x^3 | | 17x+3x=10 | | 4x+4y-x^2+xy-y^2+21=0 | | 39+(-24)-(15)= | | 0.4c^2-7c-25=0 | | T(2T+5)=6 | | 3r^2-7r-20=0 | | T-(2t+5)-5(1-2t)=2 | | x^2-8a^2-x=8a+ax-8ax | | a^2-3a+ab-3b=0 | | w^2-wd-56d^2=0 | | 6-2a-3b+ab=0 | | 3x(x-7)=(2x+8)(x-7) | | c/4=32 | | (4x-5)(5x+3)= | | 144-100y^2= | | (4x^3-7y^3)(4x^3+7y^3)= | | 5x^2+4x+1= | | y=(5x+3)(2x-1) | | (10x-5y)/(7y-14x) | | 3x+6y=93 | | 9/y-4 | | (1+xy)ydx+(1-xy)xdy=0 | | 5(2x+2)-3+8+3(2x+3)=7+2-3 | | a-(-2)= | | 15+15(_12)= | | 7(2x-3)+2(3x+3)=3-2+5 | | x^3+4x^2+31x-30=0 | | 3x+2y=285 | | (3x+1)(3x+1)(3x+1)(3x+1)= | | 3(7+2x)=5(2x+4x) |

Equations solver categories